NAIL PLATE RESTORATION AFTER AGGRESSIVE NAIL PROCEDURES (Modern American Journal of Medical and Health Sciences, 2025)
Aggressive nail procedures ( intensive filing/grinding, frequent removal of durable coatings, prolonged exposure to solvents, trauma to the cuticle and nail folds) can lead to a decrease in the thickness and strength of the nail plate, splitting (onychoschisis), longitudinal fragility (onychorrhexis), onycholysis, and chronic inflammation of the periungual tissues. Nail restoration is determined by the physiology of growth from the matrix and the reversibility of structural changes in keratin; clinically, reducing re-trauma, normalizing hydration, and using products that improve the mechanical properties of the nail plate are important. This article summarizes the mechanisms of nail damage during cosmetic procedures and presents practical restoration measures based on clinical reviews and studies on nail barrier properties and the treatment of fragility.